COMPARISON BETWEEN KELVIN RADII AND BULK HYGROSCOPICITY OF MASS AND VOLUME BASED HYGROSCOPICITY PARAMETER FOR ATMOSPHERIC AEROSOLS - Saadu, Bello; Tijjani, B. I.; Bello, S. (FUDMA Journal of Sciences, 2020)
A mass based and volume based hygroscopicities models were applied to the data extracted from Optical Properties of Aerosols and Clouds (OPAC).The microphysical properties obtained were radii, density, refractive index, mass and volume of the atmospheric aerosols of continental average, continental clean, continental polluted, maritime tropical, maritime polluted, maritime clean, at eight different relative humidity of 0%, 50%, 70%, 80%, 90%, 95%, 98% and 99%.Using the microphysical properties, hygroscopic growth factors and effective radii of the mixtures were determined while the parameters Av and Bv for volume based and Am and Bm for mass based of the aerosols were determined using multiple regression analysis with SPSS 16.0 at each relative humidity. Although it was discovered that Bv is more dominant than Av, the R2 for all the models are greater than 90%. The significances are less than 0.05, Am>Av and Bm<Bv, therefore the two models are good for atmospheric modeling.